Diagnostic Ability of Optical Coherence Tomography Angiography Macula Vessel Density for the Diagnosis of Glaucoma Using Difference Scan Sizes. Issue 4 (April 2020) - Penteado, Rafaella C.; Bowd, Christopher; Proudfoot, James A.; Moghimi, Sasan; Manalastas, Patricia I.C.; Ghahari, Elham; Hou, Huiyuan; Shoji, Takuhei; Zangwill, Linda M.; Weinreb, Robert N.
Abstract : Précis: There is diagnostic information in the outer region of optical coherence tomography angiography (OCT-A) macula scans not available in the inner region, and this information is especially useful in the early stages of glaucoma. Purpose: The aim of this study was to evaluate the diagnostic accuracy of 3×3 and 6×6 mm 2 macula OCT-A scans for classifying healthy, mild glaucoma, and moderate to severe glaucoma eyes. Methods: Participants enrolled in the Diagnostic Innovations in Glaucoma Study (DIGS) with good quality 3×3 and 6×6 mm 2 OCT-A images of the macula acquired on the same day were included in this cross-sectional study. The area under the receiver operating characteristic (AUC) curves were calculated to assess the diagnostic accuracy of vessel density (VD) of both scan sizes for differentiating between 3 diagnostic groups. Results: Two hundred seventy-nine eyes (89 healthy, 127 with mild glaucoma, and 63 with moderate to severe glaucoma) from 190 subjects were included in this study. The VD of the outer area of the 6×6 mm 2 scan size had higher diagnostic accuracy compared with the VD of the inner area of the 3×3 mm 2 scan when differentiating between healthy and mild glaucoma (3×3 mm 2 AUC=0.71 and 6×6 mm 2 AUC=0.79, P =0.032). The VD of the outer area of the 6×6 mm 2 scans had only similar diagnostic accuracy compared with the inner area of the 3×3 mm 2 scan when differentiating between healthy and moderate to severe glaucoma eyes (AUC=0.90 for 3×3 mm 2 and 0.92 for 6×6 mm 2, P =0.279). The VD of the inner area of the 6×6 mm 2 scan size had similar diagnostic accuracy to the corresponding area of the 3×3 mm 2 scan in both diagnostic categories. Conclusion: The diagnostic accuracy of VD using the 6×6 mm 2 macula OCT-A scan was better than the 3×3 mm 2 scan when differentiating between healthy and mild glaucoma eyes, and similar to the 3×3 mm 2 scan when differentiating between healthy and moderate to severe glaucoma eyes. Abstract : Supplemental Digital Content is available in the text.